PENERAPAN TEORI GESTALT DALAM MATERI LUAS DAN KELILING BANGUN DATAR UNTUK SD/MI - Richa Aulya; Jayanti Putri Purwaningrum (JURNAL MathEdu (Mathematic Education Journal), 2021)
In the theory of gestalt learning suggests that learning is not just a relationship between stimulus and response, but there are goals that must be achieved, namely in gaining an understanding of what is being learned. The learning process can be carried out effectively if students know the learning objectives they will achieve. Therefore gestalt learning theory can support the process of students' understanding of learning by interacting with the outside world or the surrounding environment. Through learning in the surrounding environment, students can more easily digest the lessons being taught rather than just experiences and memorization. If mathematics lessons are taught using gestalt theory, students will become interested in learning because with this theory students will be allowed to solve problems and understand the concepts of the material being taught by interacting with their environment so that students will find it easier to understand the material. There are five applications of gestalt learning theory in the mathematics learning process, namely: (1) insight or insightful experience, (2) meaningful learning , (3) purposive behavior or purposeful behavior, (4) life space or living space principles, and (5) transfer in learning.